Aggressive Acute Marjolin’s Ulcer Arising in a Burn Scar - Adela Alvarez Rio; Josep Oriol Roca Mas; Daniel Navarro Sanchez; Ivan Monge Castresana; Gonzalo Joaquin Soroa Moreno; Jaime Estrada Cuxart (Case Reports in Dermatological Medicine)
Marjolin’s ulcer is one of the clinical variants of squamous-cell carcinoma. It is a highly aggressive disease that develops from chronic wounds. Almost 65% of these lesions have been diagnosed on underlying burn scars. Although the mean latency time between the primary lesion and the apparition of the ulcer is around 25 years, some cases with an early debut have been described. Squamous-cell carcinomas arising in chronic wounds are typically aggressive and are related with a poor prognosis due to their late diagnosis. Therefore, it is important to recognize symptoms that indicate malignant degeneration of chronic wounds, allowing the clinician to make an early diagnosis in order not to delay the surgical treatment that is required to improve the global survival of the patient. The time elapsed between our patient’s burn and the appearance of Marjolin’s ulcer was only 7 months, drawing attention to its fast and aggressive progression.